Implementation Physical Test Measurement in Athletics Long Jump Event Using an Application - Alfarizy, Dimas; Hartati, Hartati; Victorian, Ahmad Richard (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The study, titled "Implementation of Physical Test Measurement in Pencak Silat Sports Using an Application for Students at Palembang 13 Public Junior High School," aims to establish norms for assessing physical test results in the athletics long jump event through the use of an application. The physical test components include endurance, speed, strength, muscle power, and balance assessments. This research adopts a quantitative approach with a descriptive research design. The participants consist of 20 extracurricular athletic students specializing in the long jump at Palembang 13 Public Junior High School, comprising 13 male students and 7 female students. Data collection involves various tests, utilizing specific instruments such as the bleep test for endurance, a 30-meter sprint for speed, a 1-minute push-up test for strength, a vertical jump test for muscle explosive power, and a standing stroke test for balance. The research is conducted at Palembang 13 Public Junior High School, with the collaboration of one member from the Physical Education, Sports, and Health (Pjok) MGMP in Kota Palembang. The findings from the research on extracurricular athletic students at Palembang 13 Public Junior High School indicate that the average physical condition falls into the "very good" category with a percentage of 12%, "good" with 8%, "sufficient" with 24%, "less" with 32%, and "less once" with 25%. In conclusion, the average physical condition of extracurricular students is categorized as "less" with a percentage of 32%. Following this research, the intention is to raise awareness among students to continuously enhance and maintain their physical condition to achieve optimal success